The Dependency of Bus Voltage and Frequency in Load Shedding - Mwaniki, C; Muriithi, C; Abungu, N.O (My University, 2014)
Load shedding schemes proposed in literature so far use voltage and frequency parameters separately. The individual consideration of these indices may not be reliable or effective, and may even lead to the over load shedding problems. Analysis of under-frequency load shedding is often done using the system frequency response models. The impact of voltage variation on the frequency deviation is not considered in these models. Furthermore, the under-voltage load shedding methods that are proposed for adjusting the under-voltage relays, do not consider the frequency behavior. This paper focuses on establishing the variation and the extent of dependence of these parameters on each other whenever a power system undergoes a disturbance due to loss of a transmission line.
Keywords: Voltage stability; Frequency stability; under frequency load shedding; under voltage load shedding